Improving the Ability to Know to Build Flat Through Media Flannel boards for Mentally Retarded Children Lightweight Class V In SLB Karya Padang (Single Subjeck Research)". Thesis. Department of Special Education, Faculty of Education, Padang State University - Anggi Purnama Sari (Jurnal Penelitian Pendidikan Khusus, 2016)
This research is motivated by the problems that the researchers found in the field, which is a fifth grade child mild mental retardation who have problems in identifying Flat figure (circle, triangle, rectangle and square). From the results of the assessment, children experiencing barriers when grouping, sort flat wake of the largest to the smallest, to distinguish and name the flat wake. Therefore, researchers are working to help to improve the ability to recognize a flat wake, through the medium of the flannel board.The research is a Single Subject Research to design AB. Data analysis techniques using visual analysis graphs. Subject of research is mild mental retardation child class V. Measurement variables using percentages.Observations were carried out as many as 16 times observation, namely six times on the condition (A), and ten times on the condition (B). In the conditions of (A) the data obtained is 18%, 18%, 18%, 18%, 18%, 18%. Based on these data the child can be said to have engaged in identifying flat wake, either classify, sort, differentiate, identify and name the flat wake. While in the intervention condition (B) data were obtained (22.7%) (36.3%) (54.5%) (63.6%) (70.5%), (81.9 %), (91.9%) (95.4%) (95.4%) (95.4%). Thus, the ability of children to recognize waking up flat using a flannel board media showed an increase. Based on these results it can be concluded that the media flannel board can improve the ability to know the flat wake, for mild mental retardation children in class V SLB Karya Padang. The author hopes that teachers and schools can consider the use of media in learning to know flannel board flat wake, especially for mild mental retardation children. Keywords: Build Flat, Media Flannel Boards, Mild Mental Retardation